Effects of aluminium stress on the accumulation of cations and anions in rice and chickpea seedlings grown in solution culture - Samad, Rifat; Rashid, Parveen; Karmoker, JL (Bangladesh Journal of Botany, 2018)
Different concentrations of aluminium (10-150 μM) inhibited the accumulation of Ca2+, Mg2+, Fe2+ and PO4 3- in rice and chickpea seedlings grown in solution culture. In rice and chickpea, the intensity of inhibition of the accumulation of Ca2+, Mg2+, Fe2+ and PO4 3- enhanced with the increase in Al concentrations from 10 to 150 μM. On the contrary, application of aluminium caused a dramatic few fold increase in accumulation of Al3+ in different parts of rice and chickpea seedlings.